From dual to unified employment protection: Transition and steady state - Juan J. Dolado; Etienne Lalé; Nawid Siassi (Quantitative Economics, 2021)
Three features of real-life reforms of dual employment protection legislation (EPL) systems are particularly hard to study through the lens of standard labor-market search models: (i) the excess job turnover implied by dual EPL, (ii) the nonretroactive nature of EPL reforms, and (iii) the transition dynamics from dual to a unified EPL system. In this paper, we develop a computationally tractable model addressing these issues. Our main finding is that the welfare gains of reforming a dual EPL system are sizeable and achieved mostly through a decrease in turnover at short job tenures. This conclusion continues to hold in more general settings featuring wage rigidities, heterogeneity in productivity upon matching, and human capital accumulation. We also find substantial cross-sectional heterogeneity in welfare effects along the transition to a unified EPL scheme. Given that the model is calibrated to data from Spain, often considered as the epitome of a labor market with dual EPL, our results should provide guidance for a wide range of reforms of dual EPL systems.
Keywords: E24; J63; J65; 330; dualism; Employment protection; labor market reform